VALIDITAS LEMBAR KERJA MAHASISWA (LKM) UNTUK MATERI LOGARITMA PADA PERKULIAHAN ALJABAR DASAR DI STKIP PGRI SUMATERA BARAT (Jurnal Pelangi : Research of Education and Development, 2015)
Student difficulties in understanding the logarithm material is one of the reasons for developing student’s worksheet of Elementary Algebra for logarithm material. Another factor is that there has been no effective teaching materials that facilitate the students in the lecture. The existing reference books only convey information and have not been able to construct knowledge of students, so that they do not understand about the concept. The purpose of this research was to develop a valid student’s worksheet of Elementary Algebra subject in STKIP PGRI, West Sumatra. This research is a research development. Model of development in the research used procedural models for Instructional Development Institute (IDI). Validity was analyzed by the expert of Elementary Algebra. Once the module is validated by experts, it is obtained that the student’s worksheet of Elementary Algebra valid